Pengaruh pemberian aroma terapi bunga mawar terhadap tingkat nyeri dismenorea pada siswi SMA - Ratna Sari; Dainty Maternity; Rosmiyati Rosmiyati (Holistik Jurnal Kesehatan, 2020)
The effects of aromatherapy with rose oils in premenstrual pain and primary dysmenorrhea among high school girlsBackground : Dysmenorrhea is menstrual cramps during menstruation that usually occurs in the lower or back of the abdomen. In Indonesia the incidence of dysminorrhoea was 64.25%, which experienced primary dysmenorrhoea at 54.89% while the rest were secondary type sufferers. One non-pharmacological treatment that can be used to treat pain in disminore is to use rose aromatherapy.Purpose : To known The effects of aromatherapy with rose oils in premenstrual pain and primary dysmenorrhea  among high school girlsMethod: A quantitative  a quasy experimental approach with a two group pretest-posttest design. The population was all high school girls. The sampling technique used purposive sampling as many as 30 high school girls who has experienced of premenstrual pain and primary dysmenorrhea  . Bivariate analysis using independent t-test.Results: Obtained an average of pain during menstruation in the group before being given an intervention of 7,420, after intervention 3,767, pretest pain in the control group of 7,040, after in the control group of 7,053. The independent sample T-test results obtained p value 0,000 <0.05.Conclusion: There was a effects of aromatherapy with rose oils in premenstrual pain and primary dysmenorrhea  among high school girlsKeywords: Aromatherapy; Rose oils; Premenstrual pain; Primary dysmenorrheal; High school girlsPendahuluan: Dismenore adalah kram perut saat menstruasi yang biasa terjadi pada perut bagian bawah atau belakang. Di Indonesia angka kejadian disminorea sebesar 64,25%, yang mengalami dismenorea primer sebesar 54,89% sedangkan sisanya adalah penderita tipe sekunder. Salah satu pengobatan non farmakologi yang dapat digunakan untuk mengatasi nyeri pada disminore adalah dengan menggunakan aromatherapy mawar.Tujuan : Untuk mengetahui pengaruh pemberian minyak essensial mawar pada siswi yang mengalami dismenorea di SMA Persada Kota Bandar Lampung Tahun 2019.Metode : Penelitian kuantitatif menggunakan pendekatan quasy eksperimen dengan rancangan two group pretest-posttest design. Populasi penelitian adalah seluruh remaja putri di SMA Persada Bandar Lampung dengan sampel menggunakan purposive sampling sebanyak 30 remaja putri yang mengalami dismenore setiap menstrasi. Analisa bivariat dengan menggunakan uji t-test independent. Hasil : Diperoleh rata-rata nyeri saat menstruasi pada kelompok sebelum diberi intervensi sebesar 7,420, setelah intervensi 3,767, nyeri pretes pada kelompok kontrol sebesar 7,040, setelah pada kelompok kontrol 7,053. Hasil uji T-test sample independent diperoleh nilai p value 0,000 < 0,05.Simpulan: Ada pengaruh  nyeri dismenorea dengan pemberian minyak essensial mawar pada siswi di SMA Persada Kota Bandar Lampung Tahun 2019.